Estudo da inovação na indústria brasileira de alimentos e bebidas - Almeida, Sarah Winck de (Universidade do Vale do Rio dos Sinos, 2014)
Innovation is a term currently present in the subject of both companies and research universities. However, their approach, specifically in the food sector, lacks theoretical framework that will give you support and foundation. This study aimed to identify the characteristics that influence the formation of innovation profile of Brazilian food and beverage industry, based on qualitative data from a sample of industries attended the Anuga in Germany in 2013. Therefore, bought up visions of some authors on the concepts of innovation and its application in food industry as well as the major reasons for innovation aspects as the relationship University - Industry and fostering te chnological innovation by the government. To obtain the data we used qualitative research methodology, aiming to identify factors that influence the formation of innovation in these industries profile. This study consists of the strategic objectives of the Project NUTRITECH - FINEP, conveniado with Unisinos in 2010 (Convention No. 01.10.0510.00) which consisted of the implementation of the Technological Institute for Food for Health - itt Nutrifor. From the study, it can identify the food and beverage industry have an innovative profile with rather conservative characteristics, where the concepts are confused and product innovations are basically incremental, fear of risk. Innovations in process are just new to the company, since in general run of technologies imported from other countries. Also the companies develop innovations in general, with their own (financial and personnal) resources, exist without an established relationship with the other actors in the innovation system, a fact that deserves special attention due to its great importance in the consolidation process innovation. The conclusions resulting from this study will serve to better guide the actions of Industries, Universities and other actors in the innovation system, with respect to technological innovation in the area of food and beverage in Brazil.
Keywords: Inovação; Indústria de alimentos e bebidas; Perfil de inovação; Relacionamento universidade e empresa; Innovation; Food and beverage industry; Innovation profile; University relationship and business; ACCNPQ::Ciências da Saúde::Nutrição